STUDY OF CHRONIC STRESS IN PREGNANT WOMEN - VANDALI JYOTHI,; MANJUNATH AITHALA,; NEERJA SHASTRI, (International Journal of Pharma and Bio Sciences, 2016)
Chronic stress is one of the biopsychosocial factors that contributes to adverse pregnancy outcomes such as preterm labor, aborted fetus, delayed fetal growth, low birth weight baby etc. Chronic stress can be either due to many stressors or due to same stressor continuously for a prolonged period, which repeatedly activates autonomic nervous system and hypothalamic-pituitary-adrenal (HPA) axis without relaxation response, resulting in persistent physiologic effects. Physiologic response in turn causes malfunctioning of HPA axis to release excess cortisol, the principle stress hormone. The present study was conducted to assess the relation between the chronic stress and cortisol during pregnancy. Pregnant women were assessed for the level of stress with the help of Holmes and Rahe stress scale. 96 pregnant women were selected for the study. Equal number of non-pregnant women were included in the study as a control group. Objective measurement was done by analysing the serum cortisol levels by electrochemiluminescence immunoassay. Among 96 subjects 36 (37.5%) were mildly stressed, 34 (35.41%) were moderately stressed and 26 (27.08%) were severely stressed. There was significant increase in serum cortisol levels in stressed pregnant women when compared with the cortisol levels of nonpregnant women. Level of significance was with p< 0.05.